Pharmacogenomic Characterization and Isobologram Analysis of the Combination of Ascorbic Acid and Curcumin—Two Main Metabolites of Curcuma longa—in Cancer Cells - Ooko, Edna; Kadioglu, Onat; Greten, Henry J.; Efferth, Thomas (Frontiers in Pharmacology, 2017)
ABSTRACT Curcuma longa has long been used in China and India as anti-inflammatory agent to treat a wide variety of conditions. Here we investigated chemoprofiles of three Curcuma species and observed a great variety of phytochemicals with curcumin being among the few present in all three species. On the other hand ascorbic acid (AA) was a compound that was solely found in Curcuma longa. In the present study we explored the cytotoxic effect of a curcumin/AA combination toward human cancer cell lines. The curcumin/AA combination was assessed by isobologram analysis using the Loewe additivity drug interaction model. The drug combination showed additive cytotoxicity towards CCRF-CEM and CEM/ADR5000 leukemia cell lines as well as HCT116p53+/+ and HCT116p53-/- colon cancer cell lines, while the glioblastoma cell lines U87MG and U87MG.ΔEGFR showed additive to supra-additive cytotoxicity. Gene expression profiles predicting sensitivity and resistance of tumor cells to curcumin and AA were determined by microarray-based mRNA expressions data, COMPARE and hierarchical cluster analyses. Numerous genes involved in transcription (TFAM, TCERG1, RGS13 and C11orf31), apoptosis-regulation (CRADD, CDK7, CDK19, CD81, TOM1) signal transduction (NR1D2, HMGN1, ABCA1, DE4ND4B, TRIM27) DNA repair (TOPBP1, RPA2), mRNA metabolism (RBBP4, HNRNPR, SRSF4, NR2F2, PDK1, and TGM2), and transporter genes (ABCA1) significantly correlated with cellular responsiveness to curcumin and AA. In conclusion, the effect of the curcumin/AA combination may be determined by candidate genes and their differential expression in different tumor cell lines may explain their differing responsiveness to curcumin and AA.